Integrated Screening for Tuberculosis and HIV in Tuberculosis Contact Investigations: Lessons Learned in North Carolina. (January 2014) - Stout, Jason E.; Katrak, Shereen; Goswami, Neela D.; Norton, Brianna L.; Fortenberry, Ellen R.; Foust, Evelyn; Leone, Peter A.
Combating the syndemics of tuberculosis (TB) and HIV in the United States will require increasing efficiency as the incidence of TB declines. Fortunately, new tools such as the interferon gamma release assays can be combined with existing strategies such as opt-out HIV testing to facilitate simultaneous, integrated testing for both infections. We describe the lessons learned from our experience with integrated testing for TB and HIV in the setting of TB contact investigations in North Carolina. Integrated testing represents a unique opportunity to leverage TB and HIV program resources to enhance case detection and improve linkages to care. However, joint training in field investigations and diagnostics is critical prior to conducting contact investigations. Furthermore, integrated testing must be tightly coupled to treatment and prevention programs to reduce disease transmission and morbidity from untreated disease in communities.